2021
DOI: 10.3390/rs13071345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of k-Nearest Neighbor and Random Forest Classifiers for Mapping Forest Fire Areas in Central Portugal Using Landsat-8, Sentinel-2, and Terra Imagery

Abstract: Forest fires threaten the population's health, biomass, and biodiversity, intensifying the desertification processes and causing temporary damage to conservation areas. Remote sensing has been used to detect, map, and monitor areas that are affected by forest fires due to the fact that the different areas burned by a fire have similar spectral characteristics. This study analyzes the performance of the k-Nearest Neighbor (kNN) and Random Forest (RF) classifiers for the classification of an area that is affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 141 publications
0
10
0
Order By: Relevance
“…However, because of its high stability and its ability to perform efficient processing of large-scale data 64 , the random forest classifier is a more practical integrated learning method, and it can effectively reduce the error of a single classifier and improve the classification accuracy using multiple classifiers for voting classification. Random forest algorithms have randomness in sample and feature selection, which makes it difficult for random forest to fall into overfitting and gives it a good antinoise ability 65 , 66 . In this study, a bagging integrated random forest classification algorithm was used to predict the degree of karst rocky desertification.…”
Section: Methodsmentioning
confidence: 99%
“…However, because of its high stability and its ability to perform efficient processing of large-scale data 64 , the random forest classifier is a more practical integrated learning method, and it can effectively reduce the error of a single classifier and improve the classification accuracy using multiple classifiers for voting classification. Random forest algorithms have randomness in sample and feature selection, which makes it difficult for random forest to fall into overfitting and gives it a good antinoise ability 65 , 66 . In this study, a bagging integrated random forest classification algorithm was used to predict the degree of karst rocky desertification.…”
Section: Methodsmentioning
confidence: 99%
“…As the primary KNN adjustment parameter, the parameter k is critically important to the operation of the KNN and plays a significant role in its performance. In this work, we investigated a variety of k values, ranging from five to twenty, in order to identify the best parameter for the KNN classifier based on the lowest estimate of the root mean square error (RMSE) (Pacheco et al, 2021). We used a variety of data subsets to conduct these tests.…”
Section: B) K-nearest Neighbor Decision (Knn)mentioning
confidence: 99%
“…Sentinel-2 includes three red-edged vegetation and the SWIR bands that are highly susceptible to chlorophyll content and amend distinguishing different vegetation types and LCLU classification accuracy (Chaves et al 2020). Several studies found Sentinel-2 data with high potential in different applications such as crop classification (Hernandez et al 2020), tree species classification (Costa et al 2022, Wessel et al 2018, Persson et al 2018, mapping burned area (Pacheco et al 2021), and forest type classification (Kaplan 2021). Most of the recent studies have shown that non-parametric machine learning approaches such as Artificial Neural Network (ANN), Support Vector Machine (SVM), and Random Forest (RF) have a great potential to classify heterogeneous land covers (Wessel et al 2018, Pacheco et al 2021, Sheykhmousa et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found Sentinel-2 data with high potential in different applications such as crop classification (Hernandez et al 2020), tree species classification (Costa et al 2022, Wessel et al 2018, Persson et al 2018, mapping burned area (Pacheco et al 2021), and forest type classification (Kaplan 2021). Most of the recent studies have shown that non-parametric machine learning approaches such as Artificial Neural Network (ANN), Support Vector Machine (SVM), and Random Forest (RF) have a great potential to classify heterogeneous land covers (Wessel et al 2018, Pacheco et al 2021, Sheykhmousa et al 2020. found RF as the mostly used supervised classifier and more stable object-based image analysis (OBIA) with the highest mean accuracy of 85.81%, followed by SVM through reviewing 173 publications on supervised object-based classification.…”
Section: Introductionmentioning
confidence: 99%